Aerobic Physical Exercise as a Non-medical Intervention for Brain Dysfunction: State of the Art and Beyond - Jia, Yuxiang; Yao, Yu; Zhuo, Limin; Chen, Xingxing; Yan, Cuina; Ji, Yonghua; Tao, Jie; Zhu, Yudan (Frontiers in Neurology, 2022)
Brain disorders, including stroke, Alzheimer's disease, depression, and chronic pain, are difficult to effectively treat. These major brain disorders have high incidence and mortality rates in the general population, and seriously affects not only the patients’ quality of life, but also increases the burden of social medical care. Aerobic physical exercise, which is considered an effective adjuvant therapy for preventing and treating major brain disorders. Although the underlying regulatory mechanisms are still unknown, systemic processes may be involved. Here, this review aimed to reveal that aerobic physical exercise improved depression and several brain functions, including cognitive functions, and provided chronic pain relief. We concluded that aerobic physical exercise helps to maintain the regulatory mechanisms of brain homeostasis through anti-inflammatory mechanisms, enhanced synaptic plasticity and inhibition of hippocampal atrophy and neuronal apoptosis. In addition, we also discuss the cross-system mechanisms of aerobic exercise in regulating imbalances in brain function, such as the “bone-brain axis”. Furthermore, our findings provide a scientific basis for the clinical application of aerobic physical exercise in the fight against brain disorders.